2020
DOI: 10.1136/bmjebm-2020-111417
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the completeness of intervention reporting in Cochrane surgical systematic reviews using the TIDieR-SR checklist: a cross-sectional study

Abstract: IntroductionComplete reporting of systematic reviews of interventions is essential to the interpretation of research findings and the reproducibility of research results. The Template for Intervention Description and Replication (TIDieR) checklist—and the version specific to systematic reviews (TIDieR-SR)—was created to provide authors and researchers an evidence-based guide for reporting trial and systematic review interventions. In this study, we apply TIDieR-SR to Cochrane systematic reviews of surgical int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…29 The data extracted will include specific details about each study. Details of the evidence-based leadership interventions will be extracted following the TIDIeR (Template for Intervention Description and Replication) checklist 40 : brief name; why the intervention is essential; materials and procedures; providers and their expertise; models of delivery; location and infrastructure; sessions; tailoring; modifications; planned and actual adherence or fidelity. The intervention data will be extracted by two authors (JV and KH).…”
Section: Methods and Analysismentioning
confidence: 99%
“…29 The data extracted will include specific details about each study. Details of the evidence-based leadership interventions will be extracted following the TIDIeR (Template for Intervention Description and Replication) checklist 40 : brief name; why the intervention is essential; materials and procedures; providers and their expertise; models of delivery; location and infrastructure; sessions; tailoring; modifications; planned and actual adherence or fidelity. The intervention data will be extracted by two authors (JV and KH).…”
Section: Methods and Analysismentioning
confidence: 99%
“…The effectiveness of reporting guidelines in improving the reporting quality of publications has been proven (10). However, despite the availability of guidelines that might guide surgical technique reporting, most of the studies related to interventional surgical technique lacked complete and detailed descriptions of the surgical interventions, and some even provided only the names of the interventions (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigating the reporting qualities of the clinical trials before and after the publication of guidelines showed that the development of CONSORT [ 18 , 19 ] and STRICTA [ 20 , 21 ] led to improvements of the overall reporting qualities. Cross-sectional investigations on the quality of intervention reporting of clinical trials based on TIDieR checklist [ 22 25 ] showed that while average completion of the checklist items did not show significant changes, the evaluations allowed further understanding of the description of interventions in clinical trials. However, the description of sham needles used in acupuncture trials have been partially addressed, suggesting that controls be described in a similar manner to active intervention.…”
Section: Introductionmentioning
confidence: 99%